The Implementation of Digital Media in Integrated Learning in Schools: A Systematic Literature Review From 2020 To 2025 - Subhananto, Aprian; Ibrahimi, Raziska (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The integration of technology in modern education demands the adaptation of dynamic pedagogical strategies, one of which is through an integrated learning approach. However, the implementation of digital media in unifying various disciplines in school environments still faces challenges regarding complexity and infrastructure readiness. This study aims to analyze implementation trends, the variety of technology types, and the effectiveness of using digital learning media in integrated learning in schools. The method used is a Systematic Literature Review (SLR) by reviewing 38 selected articles published between 2020–2025. Data collection was conducted through indexed databases with strict selection using the PRISMA protocol. The results show that media usage trends have evolved from simple multimedia to advanced technologies such as Artificial Intelligence (AI), Virtual Reality (VR), and Learning Management Systems (LMS). The implementation of digital media in integrated learning models, such as STEM and Project-Based Learning (PBL), has been proven to significantly increase cognitive engagement, facilitate the understanding of abstract concepts, and support differentiated learning. In conclusion, digital media is not merely a supplementary tool but a primary catalyst that enables the creation of an integrated learning ecosystem that is adaptive, collaborative, and relevant to 21st-century skill needs. Synergy between teachers' technological readiness (TPACK) and school infrastructure support is required for the sustainability of this implementation.